2016
DOI: 10.1016/j.mod.2016.08.001
|View full text |Cite
|
Sign up to set email alerts
|

The zebrafish goosepimples/myosin Vb mutant exhibits cellular attributes of human microvillus inclusion disease

Abstract: Microvillus inclusion disease (MVID) is a life-threatening enteropathy characterised by malabsorption and incapacitating fluid loss due to chronic diarrhoea. Histological analysis has revealed that enterocytes in MVID patients exhibit reduction of microvilli, presence of microvillus inclusion bodies and intestinal villus atrophy, whereas genetic linkage analysis has identified mutations in myosin Vb gene as the main cause of MVID. In order to understand the cellular basis of MVID and the associated formation o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
22
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 38 publications
5
22
1
Order By: Relevance
“…In Myo5b morphants, dextran-positive vesicles were enriched at the apical domain of peridermal cells, demonstrating that loss of Myo5b resulted in apical endocytosis (Sonal et al, 2014). Another report investigating loss of Myo5b in zebrafish showed the presence of numerous inclusions in the proximal midgut that were in close proximity to or contiguous with the apical membrane (Sidhaye et al, 2016). In addition to these zebrafish studies, our laboratory reported the presence of maternal murine IgG inside of inclusions in Myo5b KO enterocytes (Weis et al, 2016).…”
Section: Discussionmentioning
confidence: 65%
“…In Myo5b morphants, dextran-positive vesicles were enriched at the apical domain of peridermal cells, demonstrating that loss of Myo5b resulted in apical endocytosis (Sonal et al, 2014). Another report investigating loss of Myo5b in zebrafish showed the presence of numerous inclusions in the proximal midgut that were in close proximity to or contiguous with the apical membrane (Sidhaye et al, 2016). In addition to these zebrafish studies, our laboratory reported the presence of maternal murine IgG inside of inclusions in Myo5b KO enterocytes (Weis et al, 2016).…”
Section: Discussionmentioning
confidence: 65%
“…Animal models have been developed which demonstrated that the germline or conditional deletion of the Myo5b gene in mice or its ortholog in zebrafish causes the clinical and cellular hallmarks of MVID (CartĂłn‐GarcĂ­a et al., ; Schneeberger et al., ; Sidhaye et al., ; Weis et al., ), thereby formally proving the causality between loss of myosin Vb function and MVID (CartĂłn‐GarcĂ­a et al., ). There are no reported mouse models in which Stxbp2 or Stx3 is deleted.…”
Section: Animal Models For Mvid: Vertebrates Only?mentioning
confidence: 99%
“…For instance, whereas AP-1 is renowned for basolateral sorting in cultured cells (Gravotta et al, 2012), its crucial role in apical trafficking has been characterized in vivo in C. elegans and in mouse (Shafaq-Zadah et al, 2012;Zhang et al, 2012;Hase et al, 2013). Whereas the in vitro culture of intestinal organoids derived from patients with MVID or mice deficient in genes causing MVID (Schneeberger et al, 2018;Mosa et al, 2018;Wiegerinck et al, 2014) and the mutation of myoVb/goosepimples in zebrafish (Sidhaye et al, 2016) appear to reproduce most of the cellular and structural hallmarks of MVID, these models are not suitable for systematic studies. Conversely, the in vivo, easy-to-use and screening-amenable C. elegans model has been widely used to understand intestinal polarity mechanisms; however, single deletion of the orthologs of MVID-causing genes (i.e.…”
Section: Discussionmentioning
confidence: 99%